Improvement of the Student Performance in Tropical Medicine with the Problem Based Learning Method in the Universidad del Zulia, Facultad de Medicina, Universidad del Zulia - Villalobos-Perozo, Rafael (Kasmera, 2006)
The problem based learning method (ABP) is an educational method of learning that is based on andragogy and constructivism. Student perfomance in the five semesters prior to the year 2000 were compared with the five annual periods beginning in the year 2000. Improvement of student performance was statistically proven.